Practice of Accountability Based on Non-Physical Relations in the Tenganan Pegringsingan Customary Institution - Nyoman Ari Surya Darmawan; Daniel T. H. Manurung (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
The customary institution of Tenganan Pegringsingan has accountability practices based on metaphysical relationships through rituals (ceremonies) and the use of traditional offerings (banten) while adhering firmly to the teachings of kharmaphala. This research adopts a qualitative research method with an interpretive paradigm and aligns with the ethnomethodological approach. The research informants were selected based on their competence in answering the research questions, namely the traditional leader, the traditional executor, and the local community. Rituals (ceremonies) using traditional offerings (banten) are considered very sacred and holy. This offering is part of the yadnya and bhakti of the customary community at the Tenganan Pegringsingan customary institution. Yadnya is a sacrifice that will become more meaningful for others and fellow beings if we perform it with sincerity and without expecting any reward, while bhakti is the embodiment of respect that is always based on a sense of sincerity. The skill of total surrender to God to achieve the pinnacle of success and happiness in this world and the hereafter. The foundation of those values dominates the souls of the organization's administrators in carrying out their duties. Of course, yadnya and bhakti are very important in rituals.